THE POWER OF COSTUME: DEFINING CHARACTER AND IDENTITY IN THEATRICAL PERFORMANCE - Rana, Nirbhay (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research examines the historical significance of costume design in Indian theatrical performance, focusing on its role in defining character and identity through case-based analysis. By investigating specific case studies from key historical periods and traditional Indian theater forms—Classical Sanskrit drama, Kathakali, and Parsi theater—the study explores how costumes have been utilized to convey complex character identities and cultural narratives. Each case study provides an in-depth examination of costume design practices, materials, and symbolic meanings, highlighting the profound relationship between attire and character portrayal. Drawing on primary sources such as historical texts, visual records, and contemporary accounts, this research traces the evolution of costume design in Indian theater and its impact on narrative and audience perception. Through focused analysis, the study underscores the enduring power of costume in theatrical storytelling and its significance in India's cultural heritage. This case-based approach offers comprehensive insights for historians, theater practitioners, and costume designers interested in the legacy and ongoing influence of historical costume design in Indian performance traditions.